N-terminal domain of nuclear IL-1α shows structural similarity to the C-terminal domain of Snf1 and binds to the HAT/core module of the SAGA complex - Zamostna, Blanka; Novak, Josef; Vopalensky, Vaclav; Masek, Tomas; Burysek, Ladislav; Pospisek, Martin (PLoS One, 2012)
Interleukin-1α (IL-1α) is a proinflammatory cytokine and a key player in host immune responses in higher eukaryotes. IL-1α has pleiotropic effects on a wide range of cell types, and it has been extensively studied for its ability to contribute to various autoimmune and inflammation-linked disorders, including rheumatoid arthritis, Alzheimer's disease, systemic sclerosis and cardiovascular disorders. Interestingly, a significant proportion of IL-1α is translocated to the cell nucleus, in which it interacts with histone acetyltransferase complexes. Despite the importance of IL-1α, little is known regarding its binding targets and functions in the nucleus. We took advantage of the histone acetyltransferase (HAT) complexes being evolutionarily conserved from yeast to humans and the yeast SAGA complex serving as an epitome of the eukaryotic HAT complexes. Using gene knock-out technique and co-immunoprecipitation of the IL-1α precursor with TAP-tagged subunits of the yeast HAT complexes, we mapped the IL-1α-binding site to the HAT/Core module of the SAGA complex. We also predicted the 3-D structure of the IL-1α N-terminal domain, and by employing structure similarity searches, we found a similar structure in the C-terminal regulatory region of the catalytic subunit of the AMP-activated/Snf1 protein kinases, which interact with HAT complexes both in mammals and yeast, respectively. This finding is further supported with the ability of the IL-1α precursor to partially rescue growth defects of snf1Δ yeast strains on media containing 3-Amino-1,2,4-triazole (3-AT), a competitive inhibitor of His3. Finally, the careful evaluation of our data together with other published data in the field allows us to hypothesize a new function for the ADA complex in SAGA complex assembly.
Keywords: Subcellular Fractions; proteinkinasy aktivované AMP; Protein Precursors; biologické modely; trans-aktivátory; histonacetyltransferasy; Histone Acetyltransferases; Immunoprecipitation; Saccharomyces cerevisiae Proteins; Protein Structure, Tertiary; vazebná místa; Interleukin-1alpha; Trans-Activators; subcelulární frakce; podjednotky proteinů; Saccharomyces cerevisiae; vazba proteinů; Structure-Activity Relationship; terciární struktura proteinů; lidé; imunoprecipitace; AMP-Activated Protein Kinases; Cell Nucleus; Models, Biological; genový knockout; Protein Serine-Threonine Kinases; strukturní homologie proteinů; signální transdukce; Protein Binding; Signal Transduction; proteinové prekurzory; buněčné jádro; Computational Biology; Structural Homology, Protein; interleukin-1alfa; Protein Subunits; vztahy mezi strukturou a aktivitou; Saccharomyces cerevisiae - proteiny; výpočetní biologie; Gene Knockout Techniques; protein-serin-threoninkinasy; Binding Sites; Humans